WINTER COVER CROPS ON WEED INFESTATION AND MAIZE YIELD - Cutti, Luan (2016)
The establishment of commercial crops in succession to winter cover crops that leaves a dense straw layer provides significantly suppression of weeds. The objective of this work was to evaluate the suppressive potential of winter cover crops on weed infestation in maize and its effect on the yield of the maize sown in succession. The experiment was conducted in the 2012/2013 crop season, in an area of the UFSM Campus Frederico Westphalen, State of Rio Grande do Sul. Four different species of cover crops (black oat, ryegrass, vetch and forage radish) were seeded and a fallow area was used as control. Evaluations to quantify the dry matter and chemical desiccation were performed at the full flowering period of the cover crops. Maize was sown in no-tillage system, in succession to the cover crops. The incidence and shoot dry matter of weeds (g 0.25 m-2) was evaluated 15 days after the maize emergence. The main weed species in the area were: morning-glory (Ipomoea grandifolia), wild poinsettia (Euphorbia heterophylla), large crabgrass (Digitaria sanguinalis) and purple nutsedge (Cyperus rotundus). In general, vetch and ryegrass were the winter cover crops that better suppressed the weeds evaluated. The best maize yield was found in the area previously covered with ryegrass, inferring a relation between the cover crop and suppression of weeds and crop yield.